2013
DOI: 10.1038/srep02284
|View full text |Cite
|
Sign up to set email alerts
|

Signaling efficiency of Gαq through its effectors p63RhoGEF and GEFT depends on their subcellular location

Abstract: The p63RhoGEF and GEFT proteins are encoded by the same gene and both members of the Dbl family of guanine nucleotide exchange factors. These proteins can be activated by the heterotrimeric G-protein subunit Gαq. We show that p63RhoGEF is located at the plasma membrane, whereas GEFT is confined to the cytoplasm. Live-cell imaging studies yielded quantitative information on diffusion coefficients, association rates and encounter times of GEFT and p63RhoGEF. Calcium signaling was examined as a measure of the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 52 publications
(83 reference statements)
2
20
0
Order By: Relevance
“…Confocal images of cells transfected with p63RhoGEF 580 -YFP show that p63RhoGEF 580 is localized to the plasma membrane, as has been described before2223. In contrast, cells transfected with either p63RhoGEF 619 -YFP or YFP-GEFT show only a cytosolic localization of these isoforms (Fig.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Confocal images of cells transfected with p63RhoGEF 580 -YFP show that p63RhoGEF 580 is localized to the plasma membrane, as has been described before2223. In contrast, cells transfected with either p63RhoGEF 619 -YFP or YFP-GEFT show only a cytosolic localization of these isoforms (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Previous studies have shown that p63RhoGEF 580 is localized to the plasma membrane because of the palmitoylation of one or more cysteines at its the N-terminus2223. In depth sequence analysis of the first 30 amino acids shows that the N-terminus, including cysteines, of p63RhoGEF 580 is well conserved throughout the whole subphylum vertebrata (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations